Integration and Excision of a Newly Discovered Bacteroides Conjugative Transposon, CTnBST - Wesslund, Neil A. (American Society for Microbiology, 2007)
Conjugative transposons (CTns) are major contributors to the spread of antibiotic resistance genes among Bacteroides species. CTnBST, a newly discovered Bacteroides conjugative transposon, carries an erythromycin resistance gene, ermB, and previously has been estimated to be about 100 kbp in size. We report here the locations and sequencing of both of its ends. We have also located and sequenced the gene that catalyzes the integration of CTnBST, intBST. The integrase gene encodes a 377-amino-acid protein that has the C-terminal R-K-H-R-H-Y motif that is characteristic of members of the tyrosine recombinase family of integrases. DNA sequence comparisons of the ends of CTnBST, the joined ends of the circular intermediate, and the preferred site into which the circular form of CTnBST had integrated revealed that the preferred integration site (attB1) contained an 18-bp sequence of identity to the crossover region, attBST, on CTnBST. Although this site was used in about one-half of the integration events, sequence analysis of these integration events revealed that both CTnBST and a miniature form of CTnBST (miniBST) integrated into a variety of other sites in the chromosome. All of the sites had two conserved regions, AATCTG and AAAT. These two regions flanked a 2-bp sequence, bp 10 and bp 11 of the 18-bp sequence, that varied in some of the different sites and sometimes in the attBST sequences. Our results suggest that CTnBST integrates site selectively and that the crossover appears to occur within a 12-bp region that contains the two regions of conserved sequences.